Entanglement Quantification and Classification: A Systematic Literature Review - Amirul Asyraf Zhahir; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan; Siti Munirah Mohd; Mohamed Ridza Wahiddin (The Science and Information (SAI) Organization, 2024)
Indexed by WOS/SCOPUS/ERA